Coordinator Discovery and Association in Beacon-Enabled IEEE 802.15.4 Network. (31st October 2013) - Hussain, Faisal Bashir; Pyun, Jae-Young
Abstract : End devices in beacon-enabled IEEE 802.15.4 network rely on passive scan to find the coordinator for association. The latency of coordinator discovery depends on coordinator's beacon interval length. If beacon interval is long then more time is required for successful discovery and vice versa. The latency of association message exchange in IEEE 802.15.4 is considerably high due to response wait time. It is the time during which the coordinator registers the device and assigns a network address. The overall time required for successful discovery and association is inadequate to support connectivity of mobile devices in short range IEEE 802.15.4 networks. To decrease this time, we propose a coordinator assisted passive discovery and association scheme for mobile end devices in IEEE 802.15.4 networks. The proposed scheme decreases the beacon interval of the coordinators that are close to mobile devices for prompt neighboring coordinator(s) discovery. Also, it eliminates the need for response wait time during association based on early registration mechanism. Simulation analysis shows that the proposed scheme ensures fast passive discovery and association with the coordinator, irrespective of beacon interval length.